Secreted factors from cultured dental pulp stem cells promoted neurite outgrowth of dorsal root ganglion neurons and ameliorated neural functions in streptozotocin‐induced diabetic mice. Issue 1 (21st June 2019) - Miura‐Yura, Emiri; Tsunekawa, Shin; Naruse, Keiko; Nakamura, Nobuhisa; Motegi, Mikio; Nakai‐Shimoda, Hiromi; Asano, Saeko; Kato, Makoto; Yamada, Yuichiro; Izumoto‐Akita, Takako; Yamamoto, Akihito; Himeno, Tatsuhito; et al.
Abstract: Aims/Introduction: Transplantation of stem cells promotes axonal regeneration and angiogenesis in a paracrine manner. In the present study, we examined whether the secreted factors in conditioned medium of stem cells from human exfoliated deciduous teeth (SHED‐CM) had beneficial effects on diabetic polyneuropathy in mice. Materials and Methods: Conditioned medium of stem cells from human exfoliated deciduous teeth was collected 48 h after culturing in serum‐free Dulbecco's modified Eagle's medium (DMEM), and separated into four fractions according to molecular weight. Dorsal root ganglion neurons from C57BL/6J mice were cultured with SHED‐CM or DMEM to evaluate the effect on neurite outgrowth. Streptozotocin‐induced diabetic mice were injected with 100 μL of SHED‐CM or DMEM into the unilateral hindlimb muscles twice a week over a period of 4 weeks. Peripheral nerve functions were evaluated by the plantar test, and motor and sensory nerve conduction velocities. Intraepidermal nerve fiber densities, capillary number‐to‐muscle fiber ratio, capillary blood flow and morphometry of sural nerves were also evaluated. Results: Conditioned medium of stem cells from human exfoliated deciduous teeth significantly promoted neurite outgrowth of dorsal root ganglion neurons compared with DMEM. Among four fractions of SHED‐CM, the only fraction of <6 kDa promoted the neurite outgrowth of dorsal root ganglion neurons. In addition, SHED‐CM significantly prevented decline in sensory nerve conduction velocities compared with DMEM in diabetic mice. Although SHED‐CM did not improve intraepidermal nerve fiber densities or morphometry of sural nerves, SHED‐CM ameliorated the capillary number‐to‐muscle fiber ratio and capillary blood flow. Conclusions: These results suggested that SHED‐CM might have a therapeutic effect on diabetic polyneuropathy through promoting neurite outgrowth, and the increase in capillaries might contribute to the improvement of neural function. Abstract : In this study, we examined whether the secreted factors could be collected from conditioned medium of stem cells from human exfoliated deciduous teeth had beneficial effects on diabetic polyneuropathy. Conditioned medium of stem cells from human exfoliated deciduous teeth might have a therapeutic effect on diabetic polyneuropathy through promoting neurite outgrowth, and the increase in capillaries might contribute to the improvement of neural function.